765 EFFECTIVENESS OF AROMATHERAPY IN MANAGING BEHAVIOURAL AND PSYCHOLOGICAL SYMPTOMS OF DEMENTIA: A MIXED METHODS: SYSTEMATIC REVIEW. (8th March 2022) - Li, B S Y; Chan, C W H; Wong, I K Y; Yu, Y H U; Li, M
Abstract: Introduction: Over 90% older persons with dementia (PWD) exhibit behavioural and psychological symptoms of dementia (BPSD) during their illness, which is the most prominent and distressing manifestation for PWD and caregivers. Aromatherapy has demonstrated its effectiveness in BPSD management in previous studies. However, previous studies and systematic reviews have shown inconsistent findings, and no review has been done on qualitative studies. The aim of this review was to identify and review the evidence from quantitative and qualitative studies of the effectiveness of aromatherapy on BPSD management, for PWD and caregivers. Methods: Joanna Briggs Institute (JBI) methodology for mixed method systematic review with convergent segregated approach was followed. 28 English and Chinese databases were searched for published and unpublished studies. The titles, abstracts, and full-texts were screened by two reviewers based on pre-specified criteria, and methodological quality was assessed with JBI critical appraisal tools. Quantitative synthesis including meta-analysis by Review Manager 5.4, qualitative synthesis including meta-aggregation, and integration of both evidence were performed. Results: Total 8, 264 articles were retrieved. After screening, 24 studies (12 randomised controlled trials, 10 quasi-experimental studies, 2 qualitative studies) were included. Most of the studies with moderate methodological quality. Some inconsistent findings regarding the effectiveness of aromatherapy in reducing the severity of BPSD, and insufficient adherence monitoring were reported in the included studies. Significant improvement in PWD's QoL and caregivers' distress and burden, positive experience from the caregivers, as well as very low adverse effects (and no adverse effect for aromatherapy inhalation) to PWD were reported in some of the studies. Conclusion: Aromatherapy, especially in inhalation approach, might be regarded as a potentially safe and effective strategy for BPSD management with positive effects to PWD and caregivers. More structuralised and comparable studies with sufficient sample size and adherence monitoring are needed to obtain more conclusive findings.